2020
DOI: 10.3390/w12112991
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Mariculture Effluent: Characterization and Management Tools

Abstract: While marine aquaculture, or mariculture, has been growing rapidly and globally in recent decades, many environmental concerns remain to be fully addressed to achieve its long-term goal of sustainable development. This paper aims to provide a synthesized perspective on these issues by reviewing and discussing the characterization, transport, and current modelling and management tools associated with effluents released from mariculture sites. Specifically, we examined the effluent characteristics and behavior f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 114 publications
0
22
0
Order By: Relevance
“…This seems to be especially relevant in the case of the marine fish farm facility (TP- 6), where differences in the temporal distribution of the farming processes (feeding, use of chemicals, water recirculation, waste load, etc.) may affect the temporal content and speciation of metals significantly [ 40 ]. Differences in the physicochemical characteristics of the analyzed effluents.…”
Section: Resultsmentioning
confidence: 99%
“…This seems to be especially relevant in the case of the marine fish farm facility (TP- 6), where differences in the temporal distribution of the farming processes (feeding, use of chemicals, water recirculation, waste load, etc.) may affect the temporal content and speciation of metals significantly [ 40 ]. Differences in the physicochemical characteristics of the analyzed effluents.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors indicated that metabolic waste, feces and some uneaten feed pellets which included high amount of nitrogen in put made by the fish farm might reason the raised phytoplankton biomass (i.e. concentration of chlorophyll-a) and particulate organic matter in the sea water (Kaspar et al, 1988;Wang, et al, 2020). Cheshuk et al (2003) observed that there was no difference in the growth and condition index of bivalves at a distance of 70, 100, 500, 1200m from the fish cage.…”
Section: Discussionmentioning
confidence: 99%
“…Driven by the world population growth demand, mariculture industry had developed rapidly [1,2]. A large amount of wastewater produced by the marine aquaculture industry, characterized by high salinity and a large amount of suspended solids, nitrogenous compounds, and organic matter, is directly discharged into the environment, which would cause great harm to the environment [3]. Marine aquaculture wastewater could be treated by physical chemical or biological methods, among which biological methods have the unique advantage of reducing costs [4][5][6].…”
Section: Introductionmentioning
confidence: 99%